2011
DOI: 10.5751/es-04308-160413
|View full text |Cite
|
Sign up to set email alerts
|

Social-ecological Resilience and Biodiversity Conservation in a 900-year-old Protected Area

Abstract: ABSTRACT. Protected areas are increasingly being recognized as coupled social-ecological systems, whose effectiveness depends on their resilience. Here I present a historical profile of an individual case study, the New Forest (England), which was first designated as a protected area more than 900 years ago. Uniquely, a traditional pattern of land use has been maintained ever since, providing a rare opportunity to examine the resilience of an integrated social-ecological system over nine centuries. The New For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…First, resilience has been applied widely to SESs and is increasingly being used to help understand, manage, and govern complex SESs (Walker et al 2002, Ostrom 2007. For example, it has been applied to political ecology and resource management (Berkes et al 1998, Berkes 1999, as well as to a variety of specific ecosystems that include: rangelands (Anderies 2002); lakes and wetlands (Gunderson 2001, Olsson et al 2004); coral reefs (Hughes et al 2005); a protected area (Newton 2011); and an evolving urban system (Bures and Kanapaux 2011). Step 1 -ecosystem services supply and demand assessment;…”
Section: An Esf Toolkit For Economic Empowerment Must Consider Resilimentioning
confidence: 99%
“…First, resilience has been applied widely to SESs and is increasingly being used to help understand, manage, and govern complex SESs (Walker et al 2002, Ostrom 2007. For example, it has been applied to political ecology and resource management (Berkes et al 1998, Berkes 1999, as well as to a variety of specific ecosystems that include: rangelands (Anderies 2002); lakes and wetlands (Gunderson 2001, Olsson et al 2004); coral reefs (Hughes et al 2005); a protected area (Newton 2011); and an evolving urban system (Bures and Kanapaux 2011). Step 1 -ecosystem services supply and demand assessment;…”
Section: An Esf Toolkit For Economic Empowerment Must Consider Resilimentioning
confidence: 99%
“…For a protected area to be effective, it is important that managers address the factors responsible for biodiversity loss (Newton 2011). It is thus strongly recommended that elephant densities in the AENP be reduced and that the population be maintained at the stocking rates and distribution patterns recommended to maintain biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…Protected areas are subjected to both natural and human-induced disturbances (e.g., drought, poaching, water abstraction, and political change), and effective management approaches are required to enable conservation objectives to be achieved while ensuring that human needs are met (Newton 2011). Protected areas can thus be viewed as linked social-ecological systems, consisting of a suite of actors (managers, tourists, animals, plants) that cooccur in and around the protected areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of socialecological systems, Carpenter et al (2005) suggested that ecological resilience cannot be measured directly, but must be estimated by means of resilience surrogates, namely indirect proxies that are derived from theory. Methods of identifying such surrogates include stakeholder assessments, model explorations, historical profiling and case study comparison (Carpenter et al 2005), which can potentially be applied to forested systems (Newton 2011). Brand and Jax (2007) consider situations where it is possible to identify the key controlling variables.…”
Section: Measuring Resiliencementioning
confidence: 99%